ДОСЛІДЖЕННЯ ПІДХОДІВ ДО ПОБУДОВИ СКАНУЮЧОГО ПРИСТРОЮ НА ОСНОВІ БЕЗКОНТАКТНОГО МАГНІТОЕЛЕКТРИЧНОГО ДВИГУНА ЗВОРОТНО-ОБЕРТОВОГО РУХУ - Акинін, К.П.; Кіреєв, В.Г.; Філоменко, А.А.; Лавриненко, В.А.; Вертелєва, О.В. (Інститут електродинаміки НАН України, Київ, 2023)
The paper presents the results of studies of approaches to the development of a scanning device based on a specialized brushless magnetoelectric motor of return-rotary motion. The structures are described and a comparison is made of servo systems with motors both with an elastic magnetic coupling between the stator and the rotor, and without such coupling. The dependences of the accuracy of a given sawtooth signal processing and the stator current effective value on the parameters of the servo systems, the values ​​of the coefficients of elasticity and viscosity of the motor, as well as the relative value of the duration of the linear interval of the reference sawtooth signal are determined. It is shown that the reduction of the stator current effective value is achieved by introducing an elastic magnetic coupling between the stator and the rotor, as well as limiting the second derivative when forming the process of resetting the reference sawtooth signal. Ref. 8, fig. 9, tabl. 3.